Preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food

Modified electrode sheets were prepared by electrodepositing nanogold on the surface of the Prussian blue analog cube CoFe-PBA and combining thiol-modified ciprofloxacin aptamer, which solved the problem of insufficient detection performance of ciprofloxacin in the prior art. , achieving high sensitivity and high reliability detection effects.

CN118858397BActive Publication Date: 2024-12-20ZHENCUI (JIANGSU) ENZYME TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410997704.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-20
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

In the prior art, the electrochemical sensors used to detect ciprofloxacin residues in food have poor performance, and the target selectivity, stability and reproducibility are insufficient, making it difficult to effectively detect the residues of ciprofloxacin in domestic water and milk.

Method used

采用普鲁士蓝类似物立方体CoFe-PBA作为电化学基底材料,通过表面电沉积纳米金,并结合巯基修饰的环丙沙星适配体,制备出改性电极片,增强导电性能和靶标选择性,实现对环丙沙星的定量分析。

Benefits of technology

It realizes high sensitivity detection of ciprofloxacin, has a wide linear range and a low detection limit, and provides a new analysis method to ensure the reliability and environmental safety of the detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118858397B_ABST
    Figure CN118858397B_ABST
Patent Text Reader

Abstract

The invention relates to the field of photoelectric sensors, and in particular to a preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food. The preparation method comprises the following steps: synthesis of a Prussian blue analogue cube CoFe-PBA; electroplating nano-gold on the surface of the CoFe-PBA to obtain a Prussian blue analogue cube A&C electrode sheet with nano-gold deposited on the surface; modifying the surface of the A&C electrode sheet with a thiol-modified ciprofloxacin aptamer CIP·Apt to obtain a modified A&C electrode sheet, that is, to obtain an electrochemical sensor. The invention electroplates nano-gold on the surface of the Prussian blue analogue cube, and then uses the nano-gold as a medium to combine the thiol-modified ciprofloxacin aptamer. The provided electrochemical sensor has high detection sensitivity, wide linear range, low detection limit, strong selectivity for ciprofloxacin, and has good application value and application prospect in the fields of environment, biology, medicine, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photoelectric sensors, and in particular to a preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food. Background Art

[0002] Ciprofloxacin (CIP) is a synthetic third-generation quinolone antibiotic. Its antibacterial activity against almost all bacteria is 2-4 times stronger than that of norfloxacin and enoxacin. As a common veterinary drug, CIP has the strongest antibacterial activity against Gram-negative bacteria among the fluoroquinolones currently used in veterinary clinical practice; it also has a strong effect on Gram-positive bacteria. In addition, it also has a strong antibacterial effect on mycoplasma anaerobic bacteria and Pseudomonas aeruginosa. Its hydrochloride is often used clinically to treat respiratory, urinary, intestinal and other infectious diseases. In addition, some studies have pointed out that enrofloxacin (ENR) can be converted into ciprofloxacin by specific enzymes in livestock, and then excreted with livestock excrement. This means that a series of drug residue problems caused by the abuse of ENR will also be accompanied by CIP residues. In fact, thanks to the significant advantages of CIP as a veterinary drug, the problem of CIP abuse cannot be ignored. Therefore, it is also crucial to establish a suitable analytical method for detecting CIP in water samples and dairy products.

[0003] Prussian blue analogue (PBA) is a kind of classic metal organic framework structure. It has a large volume, specific surface area, better stability and adjustable pore size and is widely used. However, in the prior art, PBA is directly used as an electrochemical material substrate, and the performance of the sensor finally prepared needs to be improved. For example, patent technical document CN110330036A discloses an electrode material for aptamer sensor, an aptamer sensor and a preparation method thereof. The invention uses MnO2 / Fe2O3@amorphous carbon composite material, nucleic acid aptamer sensor and a preparation method and application thereof. The invention obtains an electrode material for aptamer sensor by calcining the prepared manganese cobalt Prussian blue analogue. However, the aptamer sensor prepared by this method has poor selectivity, stability and reproducibility for the target.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food. The electrochemical sensor has high photoelectric responsiveness and has the advantages of rapid and sensitive detection, and provides a new analytical method for the detection of ciprofloxacin residues in domestic water and milk.

[0006] Based on the above purpose, the present invention provides a preparation method and application of an electrochemical sensor for detecting ciprofloxacin residues in food.

[0007] A method for preparing an electrochemical sensor for detecting ciprofloxacin residues in food, characterized in that it comprises the following steps:

[0008] Step A1. Synthesis of Prussian blue analogue cubic CoFe-PBA;

[0009] Step A2. Electrodepositing nano-gold on the surface of CoFe-PBA to obtain a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface;

[0010] Step A3. The surface of the A&C electrode sheet is modified with a thiol-modified ciprofloxacin aptamer CIP·Apt to obtain a modified A&C electrode sheet, that is, an electrochemical sensor.

[0011] Preferably, it is characterized in that the synthesis process of the Prussian blue analog CoFe-PBA in step A1 is as follows:

[0012] Step B1. Dispersing cobalt nitrate hexahydrate powder and sodium citrate dihydrate in deionized water and stirring to obtain solution A;

[0013] Step B2. Disperse potassium ferrocyanide in deionized water and stir to obtain solution B;

[0014] Step B3. Add solution B to solution A and let stand for 25-35 min to obtain solution C;

[0015] Step B4. Solution C is centrifuged, and the obtained solid is washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 60° C. to obtain CoFe-PBA.

[0016] Preferably, the usage ratio of the cobalt nitrate hexahydrate powder, sodium citrate dihydrate and deionized water in step B1 is 0.21-0.23 g: 0.28-0.30 g: 48-52 mL.

[0017] Preferably, the dosage ratio of potassium ferrocyanide and deionized water in step B2 is 0.16-0.18 g: 48-52 mL.

[0018] Preferably, it is characterized in that the preparation method of the A&C electrode sheet in step A2 is as follows:

[0019] Step C1. Disperse CoFe-PBA in deionized water, and perform ultrasonic treatment for 28-32 minutes to obtain a CoFe-PBA suspension. Drop the CoFe-PBA suspension onto a fluorine-doped tin oxide glass electrode FTO, and dry at 110-120° C. to obtain a CoFe-PBA / FTO electrode.

[0020] Step C2. Immerse the CoFe-PBA / FTO electrode in a tetrahydrate chloroauric acid electrolyte solution, perform electrodeposition on the surface of CoFe-PBA to obtain an A&C composite material electrode sheet, immerse the A&C composite material electrode sheet in deionized water to clean the surface, and then dry it in the dark at room temperature to obtain an A&C electrode sheet.

[0021] Preferably, the dosage ratio of CoFe-PBA, deionized water and CoFe-PBA suspension in step C1 is 13-17 mg: 4-6 mL: 34-36 μL;

[0022] The concentration of the tetrahydrate chloroauric acid electrolyte in step C2 is 0.01%;

[0023] The voltage during the electrodeposition in step C2 is -0.2V, and the duration of the electrodeposition is 180-220s.

[0024] Preferably, the preparation process of the modified A&C electrode sheet in step A3 is as follows:

[0025] Thiol-modified ciprofloxacin CIP·Apt was dissolved in a buffer solution and incubated at room temperature for 50-60 minutes to prepare a CIP·Apt mixed solution. The CIP·Apt mixed solution was drop-coated on the surface of the A&C electrode sheet and incubated at -4°C for 22-24 hours under 100% humidity. Then, 6-mercaptohexanol MCH was drop-coated on the surface and incubated for 50-60 minutes to block the unmodified area of ​​the electrode and prevent nonspecific adsorption of other reagents. The surface was then rinsed with a buffer solution to obtain a modified A&C electrode sheet.

[0026] Preferably, the buffer is a mixture of TE buffer with a pH of 8 and EDTA;

[0027] The concentration of the CIP·Apt mixed solution is 500 nM;

[0028] The dosage ratio of the CIP·Apt mixed solution and 6-mercaptohexanol MCH is 33-37 μL: 8-12 mL;

[0029] The concentration of the 6-mercaptohexanol MCH is 1 mM.

[0030] The invention discloses an application of an electrochemical sensor for detecting ciprofloxacin residue in food. The electrochemical sensor is used for detecting ciprofloxacin in domestic water and milk.

[0031] Preferably, the detection of ciprofloxacin in domestic water comprises the following steps:

[0032] Step S1. Drawing of a standard curve: The electrochemical sensor and ciprofloxacin CIP were incubated together at room temperature in the dark for 90 minutes to obtain a standard solution with a ciprofloxacin concentration range of 20-120 nM. After washing with PBS buffer, an electrochemical workstation was used to perform a current test, and the photoelectric signal was linearly fitted with the ciprofloxacin concentration to obtain a ciprofloxacin concentration standard curve;

[0033] Step S2. Measure the recovery rate of sample addition: add ciprofloxacin CIP to domestic water, incubate the obtained liquid with the electrochemical sensor for 90 minutes, wash with PBS buffer, and use a CHI-660E electrochemical workstation to measure the current of the three-electrode system. Use differential pulse voltammetry, with the prepared electrochemical sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode to perform current testing and calculate the recovery rate.

[0034] Preferably, the detection of ciprofloxacin in milk comprises the following steps:

[0035] Step R1. Drawing of a standard curve: The electrochemical sensor and ciprofloxacin CIP were incubated together at room temperature in the dark for 90 minutes to obtain a standard solution with a ciprofloxacin concentration range of 20-120 nM. After washing with PBS buffer, an electrochemical workstation was used to perform a current test, and the photoelectric signal was linearly fitted with the ciprofloxacin concentration to obtain a ciprofloxacin concentration standard curve;

[0036] Step R2. Sample pretreatment: acetonitrile was added to the milk to precipitate the protein, and then the mixed suspension was subjected to ultrasonic treatment for 15 min, and then centrifuged at 4200 rpm for 10 min, and then the obtained supernatant was filtered through a 0.22 μm filter membrane to obtain the treated milk;

[0037] Step R3. Measure the recovery rate of the sample addition: add ciprofloxacin CIP to the treated milk, incubate the resulting liquid with the electrochemical sensor for 90 minutes, wash with PBS buffer, and use a CHI-660E electrochemical workstation to measure the current of the three-electrode system. Use differential pulse voltammetry, with the prepared electrochemical sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode to perform current testing and calculate the recovery rate.

[0038] Among them, Prussian blue analogs are used as an electrochemical substrate material. Nanogold is electrodeposited on the surface of Prussian blue analog cubes, and used as a medium to bind to thiol-modified ciprofloxacin aptamers. Ciprofloxacin specifically binds to the thiol-modified ciprofloxacin aptamer, which can change the steric hindrance of the electrode surface, and then change the current flowing through the working electrode surface, and then achieve quantitative analysis of ciprofloxacin through electrochemical technology.

[0039] The present invention utilizes the electrodeposition technology to electrodeposit nano-gold on the surface of a Prussian blue analog cube, thereby enhancing the conductivity of the surface. In addition, the nano-gold can also be used to fix the thiol-modified ciprofloxacin aptamer through a gold-sulfur bond, thereby enhancing the selectivity of the entire electrochemical sensor to the target. Since the configuration of the aptamer changes after specific binding with the target, the steric hindrance changes, thereby affecting the magnitude of the current passing through the working electrode surface, and establishing a corresponding relationship between the degree of change of the current signal and the concentration of ciprofloxacin, a new analytical method is provided for the detection of CIP residues in domestic water and milk, which is helpful to protect public health and environmental safety.

[0040] Beneficial effects of the present invention:

[0041] The electrochemical sensor provided by the present invention has high detection sensitivity, wide linear range and low detection limit. The electrochemical sensor is modified by ligand / aptamer and has strong selectivity for ciprofloxacin, so that the detection result has high reliability.

[0042] The present invention electrodeposits nanogold on the surface of a Prussian blue analog cube, and then uses the nanogold as a medium to bind a thiol-modified ciprofloxacin aptamer, wherein ciprofloxacin is specifically bound to the thiol-modified ciprofloxacin aptamer, thereby changing the steric hindrance of the electrode surface, thereby changing the magnitude of the current flowing through the working electrode surface, and increasing the conductivity.

[0043] The electrochemical sensor provided by the present invention has a good linear relationship between the photocurrent signal intensity and the ciprofloxacin concentration within a certain range, can realize effective detection of ciprofloxacin, and has good application value and application prospects in the fields of environment, biology and medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 The design process and application of the electrochemical sensor in the present invention;

[0046] Figure 2 The microstructure and SEM analysis diagram of the Prussian blue analogue cubic CoFe-PBA and the Prussian blue analogue cubic A&C electrode sheet with nano-gold deposited on the surface in the present invention: Figure 2 A shows that the Prussian blue analog cubic A&C electrode sheet presents a regular six-sided cubic structure; Figure 2 B shows that nearly spherical AuNPs were successfully deposited on the surface of the Prussian blue analog CoFe-PBA; Figure 2 D shows that nearly spherical AuNPs were successfully deposited on the surfaces of multiple Prussian blue analogs, cubic CoFe-PBA;

[0047] Figure 3 The SEM image and elemental diagram of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface in the present invention: Figure 3 A is the SEM image of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 3 Figures B and ac are elemental images of Prussian blue analog cubic A&C electrode sheets with nano-gold deposited on the surface;

[0048] Figure 3 C is the energy dispersive spectroscopy image of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface;

[0049] Figure 4 XRD and FT-IR images of Prussian blue analog cubic A&C electrode sheets with nano-gold deposited on the surface: Figure 4 A is the XRD image of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 4 B is the FT-IR image of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface;

[0050] Figure 5 The XPS full spectrum of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface, the HR-XPS image of C, the HR-XPS image of N, the HR-XPS image of Fe, the HR-XPS image of Co and the HR-XPS image of Au: Figure 5 A is the full XPS spectrum of the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface;

[0051] Figure 5 B is the HR-XPS image of C in the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 5 C is the HR-XPS image of N in the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 5D is the HR-XPS image of Fe in the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 5 E is the HR-XPS image of Co in the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Figure 5 F is the HR-XPS image of Au in the Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface;

[0052] Figure 6 CV diagram of the electrochemical sensor after step-by-step construction ( Figure 6 A); EIS spectrum of electrochemical sensors after step-by-step construction ( Figure 6 B); Cyclic voltammetry curves at different scan rates ( Figure 6 C); Linear regression curve of redox peak current under different scanning speed conditions and the square root of the corresponding scanning speed ( Figure 6 D)

[0053] Figure 7 The optimization diagram of the conditions for different CoFe-PBA suspension drop coating amounts and different incubation times after drop coating ( Figure 7 A); Optimization diagram of conditions for Au NPs electrodeposition at different time periods ( Figure 7 B);

[0054] Figure 8 The bar graph is the current response after incubation of other interfering substances with the electrochemical sensor ( Figure 8 A); Differential pulse voltammetry (DPV) curves of the electrochemical sensor before and after being placed in the electrolyte solution ( Figure 8 B);

[0055] Fig. 9 The differential pulse voltammetry (DPV) signal spectra of different concentrations of ciprofloxacin CIP after incubation with the electrochemical sensor. Fig. 9 A); Linear regression curve of ciprofloxacin CIP concentration and the current decay degree of the electrochemical sensor after incubation ( Fig. 9 B). DETAILED DESCRIPTION

[0056] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0057] Example 1: A method for preparing a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface, comprising the following steps:

[0058] Step S1. Disperse 0.21 g of cobalt nitrate hexahydrate powder and 0.28 g of sodium citrate dihydrate in 48 mL of deionized water, and stir thoroughly to obtain a light pink transparent solution, which is recorded as A;

[0059] Step S2. Disperse 0.16 g of potassium ferrocyanide in 48 mL of deionized water and stir thoroughly to obtain a light yellow transparent solution, denoted as B;

[0060] Step S3. Slowly pour solution B into solution A and let stand for 25 minutes to obtain a brown suspension. Centrifuge the obtained brown suspension, remove the supernatant, take a brown solid, and wash it with deionized water and anhydrous ethanol in turn, washing each for 3 times. Finally, place the solid obtained after washing in a 60°C oven for drying to obtain CoFe-PBA;

[0061] Step S4. Disperse 13 mg of CoFe-PBA in 4 ml of deionized water, and perform ultrasonic dispersion for 28 min to obtain a CoFe-PBA suspension. Drop 34 μL of the CoFe-PBA suspension onto a fluorine-doped tin oxide glass electrode FTO, and dry at 110° C. to obtain a CoFe-PBA / FTO electrode for later use.

[0062] Step S4. Prepare 0.01% tetrahydrate chloroauric acid solution and use it as the electrolyte solution. Immerse the dried CoFe-PBA / FTO electrode in the 0.01% tetrahydrate chloroauric acid solution. Set the chronoamperometry method to electro-deposit the CoFe-PBA surface. Set the voltage to -0.2V and the electro-deposition time to 180s. After the electro-deposition is completed, immerse the wet electrode sheet in deionized water for surface cleaning to wash away the tetrahydrate chloroauric acid remaining on the surface of CoFe-PBA. Then dry it at room temperature in the dark for later use to obtain a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface.

[0063] Example 2: A method for preparing a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface, comprising the following steps:

[0064] Step S1. Disperse 0.23 g of cobalt nitrate hexahydrate powder and 0.3 g of sodium citrate dihydrate in 52 mL of deionized water, and stir thoroughly to obtain a light pink transparent solution, which is recorded as A;

[0065] Step S2. Disperse 0.18 g of potassium ferrocyanide in 52 mL of deionized water and stir thoroughly to obtain a light yellow transparent solution, denoted as B;

[0066] Step S3. Slowly pour solution B into solution A and let stand for 35 minutes to obtain a brown suspension. Centrifuge the obtained brown suspension, remove the supernatant, take a brown solid, and wash it with deionized water and anhydrous ethanol in turn, washing each for 5 times. Finally, place the solid obtained after washing in a 60°C oven for drying to obtain CoFe-PBA;

[0067] Step S4. Disperse 17 mg of CoFe-PBA in 6 ml of deionized water, and perform ultrasonic dispersion for 32 min to obtain a CoFe-PBA suspension. Drop 36 μL of the CoFe-PBA suspension onto a fluorine-doped tin oxide glass electrode FTO, and dry at 120° C. to obtain a CoFe-PBA / FTO electrode for later use.

[0068] Step S4. Prepare 0.01% tetrahydrate chloroauric acid solution and use it as the electrolyte solution. Immerse the dried CoFe-PBA / FTO electrode in the 0.01% tetrahydrate chloroauric acid solution. Set the chronoamperometry method to electro-deposit the CoFe-PBA surface. Set the voltage to -0.2V and the electro-deposition time to 220s. After the electro-deposition is completed, immerse the wet electrode sheet in deionized water for surface cleaning to wash away the tetrahydrate chloroauric acid remaining on the surface of CoFe-PBA. Then dry it at room temperature in the dark for later use to obtain a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface.

[0069] Performance Test:

[0070] The prepared Prussian blue analogue cubic CoFe-PBA, A&C electrode sheets were characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) spectroscopy. The characterization results are as follows:

[0071] The microstructure and morphology of the Prussian blue analog cubic CoFe-PBA, A&C electrode sheet can be analyzed by scanning electron microscopy (SEM). The SEM image of the Prussian blue analog cubic CoFe-PBA shows that it presents a regular six-sided cubic structure ( Figure 2 A). The rough edges of the crystals observed in the image may be attributed to the excessively fast pouring speed when mixing the precursor solutions during the synthesis of the Prussian blue analog cubic CoFe-PBA. SEM images of the A&C electrode sheets. Compared with the former, spherical AuNPs ( Figure 2 B). When the resolution is reduced, it can be clearly seen that AuNPs are also successfully deposited on the surface of multiple Prussian blue analogues, CoFe-PBA cubes ( Figure 2 D). This is in stark contrast to the SEM image of the unelectrodeposited Prussian blue analogue, cubic CoFe-PBA ( Figure 2 C). Energy dispersive spectroscopy (EDS) analysis can reveal the elemental composition of the sample. EDS image of A&C electrode sheet ( Figure 3), showing that the core elements such as Co, Fe, and Au are distributed on the surface of the prepared composite material. The inset shows the content of each element in the selected area, proving the successful synthesis of the Prussian blue analog cubic CoFe-PBA and the successful deposition of AuNPs. The inset shows the content ratio of each element in the selected area. This also strongly proves that the preparation of the A&C electrode sheet is successful.

[0072] The powder X-ray diffraction (XRD) spectrum of AuNPs is shown in Figure 2. Figure 4 A (red line) is shown. The lattice parameters obtained from XRD measurements are consistent with the structure of the Prussian blue analogue crystal. The synthesized product has five diffraction peaks at 2θ=17.3°, 26.4°, 33.7°, 37.7°, and 51.5°. Compared with the standard XRD spectrum of the Prussian blue analogue cubic CoFe-PBA, they correspond to the five crystal planes (200), (220), (400), (420) and (422) of the Prussian blue analogue cubic CoFe-PBA, respectively, indicating that the prepared Prussian blue analogue cubic CoFe-PBA has a good crystal structure, indicating that the preparation of the Prussian blue analogue cubic CoFe-PBA is successful. In addition, the synthesized product has two diffraction peaks at 2θ=34.9° and 44.4°, corresponding to the two crystal planes of Au NPs. The above results show the successful synthesis of the Prussian blue analog cubic CoFe-PBA and the successful deposition of nano-gold Au NPs. The basic structure of the parent Prussian blue analog cubic CoFe-PBA is not destroyed after the electrodeposition of nano-gold Au NPs. As shown in FT-IR analysis ( Figure 4 B), 3500cm in the red curve -1 A sharp peak near the wave number 2200 cm-1 indicates that the prepared Prussian blue analog cubic CoFe-PBA may adsorb the residual solvent ethanol used for cleaning the material. -1 A very sharp characteristic peak near the wave number indicates the presence of -C≡N group. -1 The band at the wave number 1500cm corresponds to the presence of the MC≡N group. The above data illustrate the successful synthesis of the Prussian blue analogue cubic CoFe-PBA, which is a classic structure formed by cross-linking -C≡N with metal ions. -1The peak appearing near the wavenumber is attributed to the -COOH group, which may come from the sodium citrate bound to the surface of the nanogold AuNPs. Sodium citrate is used to act as a stabilizer in the preparation of the Prussian blue analogue cubic CoFe-PBA to prevent the formed Prussian blue analogue cubic CoFe-PBA from being too large and introducing too many water molecules. In addition, the binding energy (BE) shift in the XPS spectrum is also used to study the formation of the Prussian blue analogue cubic CoFe-PBA structure and the intrinsic electron motion characteristics of the active interface after nanogold electrodeposition. Figure 5 In the HR-XPS spectrum of N1s, there is an obvious characteristic peak at 397eV, which corresponds to the presence of the -CN group, which is consistent with the results of the previous infrared spectrum. In addition, in the HR-XPS spectrum of Fe2p and Co2p, there are obvious satellite peaks, and they are vibration peaks at a position several eV higher than the characteristic peaks, which also shows that both Co and Fe are in an oxidized state rather than a metallic state, which also explains the formation of the Prussian blue analog cubic CoFe-PBA structure. Finally, in the HR-XPS spectrum of Au4f, two obvious characteristic peaks appeared near 89eV and 85eV, corresponding to the Au4f5 / 2 and Au4f7 / 2 orbitals, respectively. The above results also illustrate the successful synthesis of the Prussian blue analog cubic CoFe-PBA structure and the successful deposition of AuNPs.

[0073] Electrochemical signal characterization: The changes in electrochemical signals during the sensor construction process were studied by analyzing the data of the constructed electrochemical sensor cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) to determine whether the sensor construction was successful. First, the CV curve was used to measure the electrochemical signal of the sensor with 0.1M KCl and 10mM [Fe(CN)6] 3- / 4- The mixed system is used as the electrolyte solution of the CV method, and the electrochemical signal detection is carried out on the working electrode modified with the material in turn according to the sensor construction process. Figure 6 During the step-by-step construction of the electrochemical sensor, the oxidation peak near 0.35 V in the CV curve corresponds to [Fe(CN)6] 3- / 4- Fe in the system 2+ Oxidized to Fe 3+ The lost electrons flow in the electrolyte solution system to form current. As the sensor materials are built step by step, the electrochemical impedance of the entire working electrode gradually increases, hindering the [Fe(CN)6] 3- / 4- The redox probe generates electrons through the surface of the working electrode due to the applied voltage, so the current signal generated gradually decreases, corresponding to Figure 6 The gradual decrease of the oxidation peak value in the ACV curve, and Figure 3-6 The increase of EIS value in B (semicircle radius). Compared with the bare FTO electrode (black line), the step-by-step compounding of materials increases the steric hindrance. As a bimetallic MOF, the Prussian blue analog cubic CoFe-PBA has a large electrochemical impedance, so the signal of the CV curve is significantly reduced compared with the bare FTO electrode (red line). After Au NPs are deposited on the surface of the Prussian blue analog cubic CoFe-PBA, thanks to the good conductivity of AuNPs, the signal of the CV curve is improved compared with the single Prussian blue analog cubic CoFe-PBA, which is manifested as an increase in CV signal and a decrease in electrochemical impedance (blue line). Finally, CIPApt is introduced. The surface of the aptamer often carries a large number of negatively charged phosphate skeletons, which will repel electrons to a certain extent, resulting in a further decrease in current response and a further increase in electrochemical impedance (green line). The above data structure also verifies the success of the step-by-step construction of the electrochemical sensor from the electrochemical level.

[0074] Optimization of experimental conditions:

[0075] In order to make the designed sensor have higher sensitivity and wider detection range, the electrochemical signal of the designed electrochemical sensor needs to be amplified as much as possible. Therefore, the design of the electrochemical sensor is optimized, mainly from the three aspects of the drop coating amount of the Prussian blue analog CoFe-PBA suspension, the incubation time after the drop coating of the Prussian blue analog CoFe-PBA suspension, and the AuNPs electrodeposition time, to ensure the best preparation conditions of the sensor. The drop coating amount of the Prussian blue analog CoFe-PBA suspension and the incubation time after the drop coating are considered comprehensively. Considering that the working area on the FTO electrode sheet is a circular area of ​​3mm, the drop coating amount is limited to the range of 20-35μL. Excessive drop coating will cause some materials to overflow and there is a risk of contamination. The incubation temperature is 120℃, and the incubation time is limited to 4-10h. When the incubation time is less than 4h, the applied material cannot be completely dried. When the incubation time exceeds 10h, some materials in the working area of ​​the FTO electrode sheet are prone to fall off due to the long incubation time. Finally, based on the optimization results of the above two restrictive conditions, the current signal of A&C / FTO is the highest when the drop volume is 30μL and the incubation time is 10h. Figure 7A), too much drop coating will cause too much steric hindrance on the working electrode surface, resulting in the weakening of the current signal, while too short an incubation time may cause the instability of the material in the electrolyte solution, resulting in the weakening of the current signal. After determining the drop coating amount and incubation time of the Prussian blue analog CoFe-PBA, the electrodeposition time of AuNPs was optimized based on the optimization results of the previous step, and the electrodeposition time range was 100-250s. Figure 7 As can be seen from B, the electrodeposition time is in the range of 100-200 s. As the electrodeposition time increases, the current signal of the prepared composite material in the electrolyte solution also increases. When the electrodeposition time reaches 250 s, the current signal has a significant decrease. It is speculated that the excessively long electrodeposition time has consumed most of the tetrahydrate chloroauric acid and there is a risk of introducing other impurities. Other impurities may exist on the surface of the deposited AuNPs, thereby affecting the magnitude of the current.

[0076] Selectivity, stability and reproducibility:

[0077] The thiol-modified ciprofloxacin aptamer CIP·Apt introduced in the sensor design can specifically bind to the target, but the structures of some fluoroquinolone antibiotics are too similar, so the designed electrochemical sensor will respond to them to a certain extent. However, some interfering substances other than these will not bind to the thiol-modified ciprofloxacin aptamer CIP·Apt. After co-incubation, they will often fall off with the flushing of PBS solution, thereby reducing the possibility of interfering substances physically binding to the surface of the electrode material. The current signal of the blank sensor is subtracted from the current signal after the sensor is co-incubated with ciprofloxacin CIP. This difference is used as a benchmark, and the same treatment is performed on other interfering substances. Figure 8 As shown in A, it can be observed that except for ofloxacin and enrofloxacin, some other interfering substances did not produce obvious responses after incubation with the sensor. Among them, I represents the change in current relative to the blank sensor after other interfering substances are incubated with the sensor, and I0 represents the change in current relative to the blank sensor after ciprofloxacin is incubated with the sensor, which is used as a reference. Overall, the designed sensor does not produce obvious responses to other types of antibiotics and other substances that may exist in milk, so the analysis method has good specificity. In addition to specificity, the stability of the sensor is also crucial. Soak the blank sensor in the electrolyte solution for 300s, and then record the relevant spectra for comparison, such as Figure 8As shown in Figure B, after standing in the electrolyte solution for 300 seconds, the peak current did not drop significantly, indicating that the prepared sensor has excellent stability. In order to investigate the reproducibility of sensor sample preparation, ten sensor samples were prepared in parallel according to the relevant experimental process, and their electrochemical signals were detected and recorded in turn under the same conditions, as shown in Figure 2. Figure 8 C. Among them, I0 represents the current response of the tenth sample, which is used as a reference, and I represents the current response of the other nine samples. The two are compared for evaluation. It can be seen from the figure that the difference between the ten samples is small. Considering the order of precedence in the parallel detection process, there is a significant upward trend between the current signals of sample 1 to sample 10. It is speculated that it may be because the sensor is placed in the air, which has an impact on the gold nanoparticles Au·NPs on the surface of the composite material. Overall, the RSD value of the current signal response of the ten samples is 3.0%, and the sample preparation reproducibility is good. The above experiments were all detected using differential pulse voltammetry (DPV), and the electrolyte solution was 0.1M KCl and 10mM [Fe(CN)6] 3- / 4- mixed system.

[0078] Analytical performance of electrochemical sensor for ciprofloxacin CIP:

[0079] Fig. 9 A shows the changing trend of DPV signal with the increase of CIP concentration. The results show that with the increase of CIP concentration, the specific binding of CIP and CIPApt causes the configuration of Apt to change, which changes the steric hindrance. At the same time, the negatively charged thiol Apt will further repel electrons in the electrolyte solution and hinder them from flowing through the surface of the electrode. Therefore, the current signal has a significant downward trend. Fig. 9 B shows the linear relationship between the concentration of added CIP and the DPV signal. The results show that within the CIP concentration range of 20-120 nM, the concentration of added CIP and the attenuation degree of the current signal have a good linear relationship. The linear regression equation is I0-I=0.00188[CIP]-0.0065(R 2 =0.9968). Wherein, I0 represents the DPV signal detected by the blank sensor, and I represents the DPV signal detected after the sensor was incubated with different concentrations of CIP.

[0080] Actual sample analysis:

[0081] The pre-treated laboratory tap water and pure milk were used as actual samples to evaluate the feasibility of the analytical method in actual samples. The tap water came from the School of Pharmacy, South Campus, Shenyang Pharmaceutical University, Xihu District, Benxi City, Liaoning Province, and the pure milk was purchased from a local supermarket in Xihu District, Benxi City. Considering that the CIP content in tap water and commercial milk is low, the standard addition method was used for detection. The recovery rate and relative standard deviation of CIP are listed in Table 3. The recovery rate RSD value is less than 2.62%. These results show that the prepared electrochemical sensor has good detection performance for CIP in milk and tap water, is not easily interfered by the matrix, and can be used for rapid detection of CIP residues in dairy products and domestic water.

[0082] Table 1 Summary of relevant instruments and sources involved in the experiment

[0083] Instrument Name Instrument source DF-101S collector type constant temperature heating magnetic stirrer Gongyi Yuhua Instrument Co., Ltd. Nicolet 6700 Fourier Transform Infrared Spectrometer ThermoFisher, USA EscaLab250XiX-ray Photoelectron Spectrometer ThermoFisher, USA X-ray diffraction spectrometer Beijing Dongxi Analytical Instruments Co., Ltd. LC-400 Low Speed ​​Centrifuge Anhui University of Science and Technology Innovation Co., Ltd. SQP-QUINTIX35-1CN electronic balance Satorius, Germany KQ-5200 Ultrasonic Cleaner Kunshan Ultrasonic Instrument Co., Ltd. Blast drying oven Tianjin Test Instrument Co., Ltd. SigMA300 Scanning Electron Microscope Zeiss CHI660E Electrochemical Workstation Shanghai Chenhua Instrument Co., Ltd.

[0084] Table 2 Summary of relevant reagents and raw materials involved in the experiment

[0085]

[0086]

[0087] Table 3 Detection of CIP in actual milk and tap water samples (n=3)

[0088]

[0089] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0090] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an electrochemical sensor for detecting ciprofloxacin residues in food, It is characterized in that The following steps are involved: Step A1. Synthesis of Prussian blue analogue cubic CoFe-PBA; Step A2. Electrodepositing nano-gold on the surface of CoFe-PBA to obtain a Prussian blue analog cubic A&C electrode sheet with nano-gold deposited on the surface; Step A3. Modifying the surface of the A&C electrode sheet with a thiol-modified ciprofloxacin aptamer CIP·Apt to obtain a modified A&C electrode sheet, that is, an electrochemical sensor; The preparation method of the A&C electrode sheet in step A2 is as follows: Step C1. Disperse CoFe-PBA in deionized water, and perform ultrasonic treatment for 28-32 minutes to obtain a CoFe-PBA suspension. Drop the CoFe-PBA suspension onto a fluorine-doped tin oxide glass electrode FTO, and dry at 110-120° C. to obtain a CoFe-PBA / FTO electrode. Step C2. Immerse the CoFe-PBA / FTO electrode in a tetrahydrate chloroauric acid electrolyte solution, perform electrodeposition on the surface of CoFe-PBA to obtain an A&C composite material electrode sheet, immerse the A&C composite material electrode sheet in deionized water to clean the surface, and then dry it in the dark at room temperature to obtain an A&C electrode sheet.

2. The method for preparing the electrochemical sensor for detecting ciprofloxacin residue in food according to claim 1, It is characterized in that The synthesis process of the Prussian blue analogue cubic CoFe-PBA described in step A1 is as follows: Step B1. Dispersing cobalt nitrate hexahydrate powder and sodium citrate dihydrate in deionized water and stirring to obtain solution A; Step B2. Disperse potassium ferrocyanide in deionized water and stir to obtain solution B; Step B3. Add solution B to solution A and let stand for 25-35 min to obtain solution C; Step B4. Solution C is centrifuged, and the obtained solid is washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 60° C. to obtain CoFe-PBA.

3. The method for preparing the electrochemical sensor for detecting ciprofloxacin residue in food according to claim 2, It is characterized in that The usage ratio of the cobalt nitrate hexahydrate powder, sodium citrate dihydrate and deionized water in step B1 is 0.21-0.23 g: 0.28-0.30 g: 48-52 mL; The usage ratio of potassium ferrocyanide and deionized water in step B2 is 0.16-0.18 g: 48-52 mL.

4. The method for preparing the electrochemical sensor for detecting ciprofloxacin residue in food according to claim 1, It is characterized in that The amount ratio of CoFe-PBA, deionized water and CoFe-PBA suspension in step C1 is 13-17 mg: 4-6 mL: 34-36 μL; The concentration of the tetrahydrate chloroauric acid electrolyte in step C2 is 0.01%; The voltage during the electrodeposition in step C2 is -0.2V, and the duration of the electrodeposition is 180-220s.

5. The method for preparing the electrochemical sensor for detecting ciprofloxacin residue in food according to claim 1, It is characterized in that The preparation process of the modified A&C electrode sheet in step A3 is as follows: The thiol-modified ciprofloxacin aptamer CIP·Apt was dissolved in a buffer solution and incubated at room temperature for 50-60 minutes to prepare a CIP·Apt mixed solution. The CIP·Apt mixed solution was drop-coated on the surface of the A&C electrode sheet and incubated at -4°C for 22-24 hours under 100% humidity. Then, 6-mercaptohexanol MCH was drop-coated on the surface and incubated for 50-60 minutes. After that, the surface was rinsed with a buffer solution to obtain a modified A&C electrode sheet.

6. The method for preparing the electrochemical sensor for detecting ciprofloxacin residue in food according to claim 5, It is characterized in that The concentration of the CIP·Apt mixed solution is 500 nM; The dosage ratio of the CIP·Apt mixed solution and 6-mercaptohexanol MCH is 33-37 μL: 8-12 mL; The concentration of the 6-mercaptohexanol MCH is 1 mM.

7. Use of an electrochemical sensor prepared by the method for preparing an electrochemical sensor for detecting ciprofloxacin residues in food according to any one of claims 1 to 6, It is characterized in that The electrochemical sensor is used for detecting ciprofloxacin in domestic water or milk.

8. The use according to claim 7, It is characterized in that The detection of ciprofloxacin in domestic water includes the following steps: Step S1. Drawing of a standard curve: The electrochemical sensor and ciprofloxacin CIP were incubated together at room temperature in the dark for 90 minutes to obtain a standard solution with a ciprofloxacin concentration range of 20-120 nM. After washing with PBS buffer, an electrochemical workstation was used to perform a current test, and the photoelectric signal was linearly fitted with the ciprofloxacin concentration to obtain a ciprofloxacin concentration standard curve; Step S2. Measure the recovery rate of sample addition: add ciprofloxacin CIP to domestic water, incubate the obtained liquid with the electrochemical sensor for 90 minutes, wash with PBS buffer, and use a CHI-660E electrochemical workstation to measure the current of the three-electrode system. Use differential pulse voltammetry, with the prepared electrochemical sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode to perform current testing and calculate the recovery rate.

9. The use according to claim 7, It is characterized in that The detection of ciprofloxacin in milk involves the following steps: Step R1. Drawing of a standard curve: The electrochemical sensor and ciprofloxacin CIP were incubated together at room temperature in the dark for 90 minutes to obtain a standard solution with a ciprofloxacin concentration range of 20-120 nM. After washing with PBS buffer, an electrochemical workstation was used to perform a current test, and the photoelectric signal was linearly fitted with the ciprofloxacin concentration to obtain a ciprofloxacin concentration standard curve; Step R2. Sample pretreatment: acetonitrile was added to the milk to precipitate the protein, and then the mixed suspension was subjected to ultrasonic treatment for 15 min, and then centrifuged at 4200 rpm for 10 min, and then the obtained supernatant was filtered through a 0.22 μm filter membrane to obtain the treated milk; Step R3. Measure the recovery rate of the sample addition: add ciprofloxacin CIP to the treated milk, incubate the resulting liquid with the electrochemical sensor for 90 minutes, wash with PBS buffer, and use a CHI-660E electrochemical workstation to measure the current of the three-electrode system. Use differential pulse voltammetry, with the prepared electrochemical sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode to perform current testing and calculate the recovery rate.